Enumerating the number of admissible stack polygons: An approach using finite automaton - Lapus, Raymond R. (Animo Repository, 2009)
Let R(H, W) be a rectangle with positively integral valued height H and width W. We consider the classes of stack polygons that can be formed inside R(H, W) in such a way that the point of origin and the base of these polygons respectively coincides with the southwest corner and the bottom portion of R(H, W). In this paper, we construct an automaton to enumerate the number of stack polygons that satisfies the above restrictions. Moreover we derive the generating function from this automaton.